HUBUNGAN ANTARA HARGA DIRI (SELF-ESTEEM) DENGAN TINGKAT STRES NARAPIDANA WANITA DI LAPAS KLAS IIA DENPASAR - Juniartha, I Gusti Ngurah (Coping: Community of Publishing in Nursing, 2015)
Go into prison is a tough adjustment for a person. Female inmates who enter prison will have an impact on the psychological form of self-esteem changes, someone who enter prisons and lived as prisoners can be a stressor factor for female prisoners. This study aims to determine the relationship between self-esteem (self-esteem) with stress levels of women prisoners in Class IIA Denpasar Prison. This study is a non-experimental studies with correlational research design using Cross-sectional approach. Sampling method in this study is purposive sampling technique with the sample was 64 study subjects. The data was collected using a questionnaire, Self-Esteem Inventory by Coopersmith (1967) and stress levels by Ahmad’s questionnaires. The study found that of 64 study subjects, the highest frequency of female inmates for the variable self-esteem was subject with intermediate self-esteem as many as 36 people (56.2%), followed by subjects with low self esteem as many as 16 people (25% ) and subjects with high self-esteem as many as 12 people (18.8%). Then while under the stress level of the subject, found subjects with mild stress levels as much as 15 people (23.4%), intermediate stress level is as many as 37 people (59.4%) and severe stress level by 12 people (18.8%). According to statistical test using the Spearman Rank test p = 0.05, found the sig. (2-tailed) = 0.011 which means the research hypothesis is accepted (Sig. (2-tailed) <p). In addition to the value obtained was -0.314 Correlation Coefficient, which means that the variable self-esteem to the level of stress has a negative relationship with the weak relationship between variables (range 0.2 - 0.399). Thus the conclusion of this study is there was a relationship between self-esteem (self-esteem) with stress levels of women prisoners in Class IIA Denpasar Prisons.
Keywords: Women Prisoners, Self Esteem, Stress Levels